2019
DOI: 10.4314/ijbcs.v12i6.26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-sickling activity of <i>Newbouldia laevis</i> P. Beauv extracts

Abstract: Sickle cell disease is a genetic disease very expanded all over the African block. In Togo like most African countries, it's one of major causes of morbidity and mortality. The available treatments are very ornamental and are most of the time remedy than cure. However, in our areas, the sicks use medicinal plants for treating themselves. It's in this scope that this study has been conducted in sight of assessing the anti-sickling activity of Newbouldia laevis extracts (leaves, roots and stem barks) based on Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These compounds belong to the polyphenol family. Polyphenols are recognised as being responsible for anti-sickle cell activity by several authors [26,27]. According to Ghosh et al [28], flavonoids improve endothelial function by activating the synthesis of vasorelaxant nitric oxide, which could therefore play an important role in the treatment of sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds belong to the polyphenol family. Polyphenols are recognised as being responsible for anti-sickle cell activity by several authors [26,27]. According to Ghosh et al [28], flavonoids improve endothelial function by activating the synthesis of vasorelaxant nitric oxide, which could therefore play an important role in the treatment of sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative phytochemical assay revealed the presence of 31.3 mg/g flavonoids in the extract. Due to the antioxidant activity of flavonoids, studies have shown that they play a significant role in the prevention and management of many chronic diseases including sickle cell diseases (John et al, 2018;Dermane et al, 2018). Thus, the observed antisickling activity may be due to the abundant flavonoids present in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals reported in this study have different pharmacological properties, hence supporting the nutritional and medicinal values of tiger nut tubers. The phytochemicals have hepatoprotective, anti-sickling, aphrodisiac, antimicrobial, anti-inflammatory, and antioxidant properties (Da Silva et al, 2012;Rehman et al, 2015;Dermane et al, 2018;Yang et al, 2020). Furthermore, anthroquinone, a phytochemical compound known to have a laxative effect and relevant in the cure for constipation (Lombardi et al, 2020), was identified, in tiger nut samples purchased from the Ado-Ekiti market.…”
Section: Discussionmentioning
confidence: 99%